Práticas de leitura propostas por professores na formação inicial em diferentes licenciaturas: investigando relatórios de estágio supervisionado - Diniz, Alline Laís Schoen (Universidade Federal do Tocantins, 2016)
This dissertation presents an analysis of reading practices as proposed by elementary teachers of various areas in their supervised teaching practice disciplines. We also investigate the official guidelines that should guide the Elementary and Secondary Education (PCN, RCTO, PCNEM, PCN+, PCEMTO e OCEM) in order to characterize the proposed school work with reading, suggested by these official documents. Under the perspective of Applied Linguistics, we discuss the teaching of reading under the light of critical literacy theories as well as the notion of gender as social action. The supervised teaching practice reports - main object of study of this research - were produced by Undergraduate students in Geography, History and Mathematics courses at Universidade Federal do Tocantins (UFT), Araguaína Campus. The research aims at: 1) Identifying the practices of reading oriented practices conducted by supervised teaching practice students in the writing of reports in response to the demands of students of school subjects of Geography, History and Mathematics to develop specific skills in these areas; 2) Identifying and describing reading practices proposed in the official curriculum guidelines for the teaching of Geography, History and Mathematics in Elementary Education; 3) Identifying and describing reading practices proposed in didactic exercises developed in Elementary Education and registered by future teachers in their reports - the final paper to be delivered for the Internship discipline; 4) Crossing the results found in previous objectives in order to identify and describe the ways of appropriation and mobilization of different knowledges about reading practices by the so called master-students and observe how these practices can contribute to the strengthening of critical literacy among students in Basic Education. Qualitative research approach was used to characterize the treatment of the investigated documents. Documentary analysis was the main research method to inform the generation of the analyzed data, which consists of supervised internship written reports produced by teachers in training from three Undergraduate courses besides the official documents mentioned above. The reading activities proposed by teachers in training in Geography and History and Mathematics undergraduate courses during the required supervised training configured as reading activities rather peculiar to the school context and quite disconnected to social practices outside school. Moreover, the frailty of reading competence - among other factors - is commonly related by master students to learning difficulties in the focused disciplines. The analysis results show that the proposed work with reading the guidelines suggested by the official guidelines investigated motivate collaborative work among teachers responsible for the disciplines which can result in more meaningful activities for student´s critical literacy.